Fiqh al-zawaj wa al-talaq wa ma'alayh al-'amal fi qanun al-ahwal al-shakhsiyah al-Imarati - Abu Rakhiyah, Majid; (3GdLHhQj, YHO Gddg eMeOs (al-Shariqah : Jami'at al-Shariqah, 2008)
Marriage ; divorce ; laws and legislation ; Islamic law ; United Arab Emirates
Keywords: Marriage (Islamic law) -- United Arab Emirates; Divorce (Islamic law) -- United Arab Emirates